2018
DOI: 10.3847/1538-4357/aacafa
|View full text |Cite
|
Sign up to set email alerts
|

Spots, Flares, Accretion, and Obscuration in the Pre-main-sequence Binary DQ Tau

Abstract: DQ Tau is a young low-mass spectroscopic binary, consisting of two almost equal-mass stars on a 15.8 d period surrounded by a circumbinary disk. Here, we analyze DQ Tau's light curves obtained by Kepler K2, the Spitzer Space Telescope, and ground-based facilities. We observed variability phenomena, including rotational modulation by stellar spots, brief brightening events due to stellar flares, long brightening events around periastron due to increased accretion, and short dips due to brief circumstellar obscu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
40
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 69 publications
(92 reference statements)
8
40
1
Order By: Relevance
“…Our results that the accretion depends on the orbital phase and is highest nearby periastron support previous observational and numerical results in the literature for DQ Tau and for eccentric binary systems in general (e.g. Mathieu et al 1997;Günther & Kley 2002a;Salter et al 2010;D'Orazio et al 2013;Farris et al 2014a;Muñoz & Lai 2016;Tofflemire et al 2017;Kóspál et al 2018;Muzerolle et al 2019). This is in agreement with the hypothesis that the accretion flow of DQ Tau can be explained by the "pulsed accretion model" (Artymowicz & Lubow 1996), according to which the accretion is highly modulated by the binaries orbital motion, peaking during periastron passages.…”
Section: Accretion Luminosity and Mass Accretion Ratesupporting
confidence: 91%
See 3 more Smart Citations
“…Our results that the accretion depends on the orbital phase and is highest nearby periastron support previous observational and numerical results in the literature for DQ Tau and for eccentric binary systems in general (e.g. Mathieu et al 1997;Günther & Kley 2002a;Salter et al 2010;D'Orazio et al 2013;Farris et al 2014a;Muñoz & Lai 2016;Tofflemire et al 2017;Kóspál et al 2018;Muzerolle et al 2019). This is in agreement with the hypothesis that the accretion flow of DQ Tau can be explained by the "pulsed accretion model" (Artymowicz & Lubow 1996), according to which the accretion is highly modulated by the binaries orbital motion, peaking during periastron passages.…”
Section: Accretion Luminosity and Mass Accretion Ratesupporting
confidence: 91%
“…This interpretation has been confirmed in the following DQ Tau accretion studies (e.g. Salter et al 2010;Tofflemire et al 2017;Kóspál et al 2018;Muzerolle et al 2019). However, while the on-average results confirm the model predictions, Tofflemire et al (2017) found a complex variability from epoch to epoch, suggesting that the material accretes from the inner edge of the CBD in a more complex way than predicted by models.…”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…Such a phase-dependent pulsed accretion process has been seen in numerous theoretical A62, page 10 of 15 studies (e.g., Günther & Kley 2002;Dunhill et al 2015;Duffell et al 2019). Time-variable spectroscopic signatures of accretion activity (e.g., through hydrogen recombination lines) correlated with the binary orbital phase have been observed in some tight (spectroscopic) binary systems (e.g., Mathieu et al 1997;Kóspál et al 2018). While the detection of pulsed accretion is usually restricted to very tight systems (because of the restricted time base), the detection of periodic streamers in GG Tau A, if confirmed, would be the first indication of such processes in a wider system.…”
Section: Accretion Streams Within the Circumbinary Gapmentioning
confidence: 99%